2013
DOI: 10.1002/art.38131
|View full text |Cite
|
Sign up to set email alerts
|

Value of Isolated IgA Anti–β2‐Glycoprotein I Positivity in the Diagnosis of the Antiphospholipid Syndrome

Abstract: Purpose To examine the prevalence of isolated IgA anti-β2Glycoprotein I (anti-β2GPI) positivity and the association of these antibodies, and a subgroup that bind specifically to domain IV/V of β2GPI, with clinical manifestations of the Antiphospholipid Syndrome (APS) in three patients groups. The pathogenicity of IgA anti-β2GPI was also evaluated in a mouse model of thrombosis. Methods Patients with systemic lupus erythematosus (SLE) from a multiethnic, multicenter cohort (LUpus in MInorities, NAture versus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
97
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(101 citation statements)
references
References 25 publications
3
97
1
Order By: Relevance
“…The diagnostic value of IgA aCL and anti-β 2 GPI antibodies has been largely ignored because this antibody isotype is commonly present with IgG and IgM antibodies. Murthy et al (8) recently reported the presence of isolated IgA anti-β 2 GPI antibodies and concluded that this isotype may identify additional patients with the clinical features of APS as well as recommended the testing for IgA antibodies when other antiphospholipid antibodies are absent and APS is suspected. discrepant results among laboratories and commonly used commercial IgA anti-β 2 GPI enzyme-linked immunoassay (ELISA) tests when testing SLE and/or APS serum samples.…”
Section: Introductionmentioning
confidence: 99%
“…The diagnostic value of IgA aCL and anti-β 2 GPI antibodies has been largely ignored because this antibody isotype is commonly present with IgG and IgM antibodies. Murthy et al (8) recently reported the presence of isolated IgA anti-β 2 GPI antibodies and concluded that this isotype may identify additional patients with the clinical features of APS as well as recommended the testing for IgA antibodies when other antiphospholipid antibodies are absent and APS is suspected. discrepant results among laboratories and commonly used commercial IgA anti-β 2 GPI enzyme-linked immunoassay (ELISA) tests when testing SLE and/or APS serum samples.…”
Section: Introductionmentioning
confidence: 99%
“…While anti-DI antibodies were related to thrombosis in the study by de Laat et al which did not differentiate between APS and lupus patients, the only study on the clinical meaning of anti-DI antibodies conducted specifically in a lupus popupulation did not evince a significant association with aPL-related clinical events [44]. On the other hand, in the same study a significant association emerged between anti-DIV/V IgA and stroke; consistently, Murthy et al observed that 77% of patients with positive for anti-DIV/V antibodies had clinical manifestations of SAPS [53].…”
Section: Resultsmentioning
confidence: 93%
“…IgA anti-β 2 GPI DIV/V titers well correlated with IgA anti-β 2 GPI titers (p<0.0001). Of the 62 patients whose samples were positive for binding of IgA to anti-β 2 GPI DIV/V, 77% had clinical manifestations of APS that included DVT, strokes, myocardial infarction, pulmonary arterial hypertension, seizures, pregnancy losses, skin ulcers, and livedo reticularis [53].…”
Section: Anti-domain IV and Anti-domain V Antibodies In Systemic Lupumentioning
confidence: 99%
“…In-house aPS/PT ELISA was performed as previously described [19]. Medium binding plates (Costar, Cambridge, USA) were coated with phosphatidyserine in chloroform/methanol 1:4 and dried overnight at 4°C.…”
Section: Measurement Of Antiphospholipid Antibodiesmentioning
confidence: 99%
“…Although antiprothrombin antibodies have not yet been included in the classification criteria of APS, they are emerging as an increasingly important supportive marker [1,[19][20][21]. We have previously reported of IgG and/or IgM antibodies against complex phosphatidylserine/prothrombin (aPS/PT) exhibiting the highest percentage of LA activity, as compared to aCL or anti-β2GPI [19] and their strong association to thrombosis and adverse pregnancy outcome, irrespective of other antiphospholipid antibodies [20,22]. The latest systematic review concluded that routine measurement of aPS/PT antibodies of IgG and/or IgM isotype in serum or plasma might be useful in establishing the thrombotic risk of patients with previous thrombosis and/or (SLE) [21].…”
Section: Introductionmentioning
confidence: 99%